ANALISIS FAKTOR KESADARAN MEMBAYAR PAJAK, PENGETAHUAN PERATURAN PERPAJAKAN, DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Anisa Putri; Nur Diana; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to analyze the effect of awareness of paying taxes, knowledge of tax regulations, and the service of the tax authorities on individual taxpayer compliance. The sample used in this study are taxpayers who have NPWP and are registered at KPP Pratama Malang Utara. At the same time, the sample used in this research is purposive sampling. The sample for this study has the following criteria: a.) taxpayers registered at KPP Pratama Malang Utara. b.) individual tax with a single job as an employee. The results of this study indicate that the awareness of paying taxes and knowledge of tax regulations do not affect individual taxpayer compliance. In contrast, the tax service variable positively affects individual taxpayer compliance.Keywords: awareness of paying taxes, knowledge of tax regulations, tax service services, and individual taxpayer compliance.